2020
DOI: 10.3389/fgene.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Clustering Reveals a Novel Subtype of Soft Tissue Sarcoma With Poor Prognosis

Abstract: Background: Soft tissue sarcomas (STSs) are heterogeneous at the clinical and molecular level and need to be further sub-clustered for treatment and prognosis. Materials And Methods: STSs were sub-clustered based on RNAseq and miRNAseq data extracted from The Cancer Genome Atlas (TCGA) through the combined process of similarity network fusion (SNF) and consensus clustering (CC). The expression and clinical characteristics of each sub-cluster were analyzed. The genes differentially expressed (lncRNAs, miRNAs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Identifying effective biomarker and constructing an ideal prognostic signature or nomogram has long been the focus of oncologists, which can individually predict the specific outcomes to guide the management of tumor patients. At present, a great number of biomarkers have been reported, and several prognostic models for sarcoma were constructed ( Benassi et al, 2015 ; Callegaro et al, 2017 , 2019 ; Yang et al, 2017 ; Huang et al, 2019 ; Raut et al, 2019 ; Zhang et al, 2019a ; Gu et al, 2020 ; Hu et al, 2020 ; Zhu et al, 2020 ). For example, MS Benassi et al (2015) reported that the expression of IGFBP7, considered a tumor stroma marker in mesenchymal-derived cells, was highly prognostic in poor metastasis-free survival for soft tissue sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying effective biomarker and constructing an ideal prognostic signature or nomogram has long been the focus of oncologists, which can individually predict the specific outcomes to guide the management of tumor patients. At present, a great number of biomarkers have been reported, and several prognostic models for sarcoma were constructed ( Benassi et al, 2015 ; Callegaro et al, 2017 , 2019 ; Yang et al, 2017 ; Huang et al, 2019 ; Raut et al, 2019 ; Zhang et al, 2019a ; Gu et al, 2020 ; Hu et al, 2020 ; Zhu et al, 2020 ). For example, MS Benassi et al (2015) reported that the expression of IGFBP7, considered a tumor stroma marker in mesenchymal-derived cells, was highly prognostic in poor metastasis-free survival for soft tissue sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MS Benassi et al (2015) reported that the expression of IGFBP7, considered a tumor stroma marker in mesenchymal-derived cells, was highly prognostic in poor metastasis-free survival for soft tissue sarcoma. Additionally, clinicopathological variables, ncRNA data, or immune cells were also confirmed as predictors and used to develop prognostic models ( Callegaro et al, 2017 , 2019 ; Yang et al, 2017 ; Huang et al, 2019 ; Raut et al, 2019 ; Zhang et al, 2019a ; Gu et al, 2020 ; Hu et al, 2020 ; Zhu et al, 2020 ). Nevertheless, clinical practice is not optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several genomic and transcriptome data have focused on exploring effective diagnostic or prognostic markers in STSs, including alternative splicing, [ 8 ] copy number variation, [ 9 ] and genes expression. [ 10 ] As one of the core elements in tumorigenesis progression, DNA methylation occurs early and frequently in regulating a variety of genomic functions. [ 11 ] DNA methylation is a posttranslational modification process, which are selectively occurred on the cytosines of 5“-CpG-3” to generates 5-methyldeoxycytidine.…”
Section: Introductionmentioning
confidence: 99%
“…Although current frontline DLBCL therapy (the standard R-CHOP chemotherapy regimen) is associated with a high complete response rates of 70-80%, 10% to 15% of DLBCL patients are refractory, and almost 40% of cases experience relapse within 2-3 years after initial response 3,4 . An enhanced International Prognostic Index (NCCN-IPI) was built to better discriminate low-and high-risk subgroups in the rituximab era, which still needs to be further investigated on the robust capacity for risk stratification in the context of targeted therapies 5,6 . Therefore, there is an urgent need to explore potential molecular mechanism and identify more key biomarkers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%